2006
DOI: 10.1136/pmj.2005.039032
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in type 2 diabetes in secondary care: association with cardiovascular risk factors

Abstract: Obesity is the rule among patients attending this hospital diabetes clinic, with 86% of those with type 2 diabetes overweight or obese. Obesity is associated with significantly worse cardiovascular risk factors in this patient group, suggesting that more active interventions to control weight gain would be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
174
4
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(211 citation statements)
references
References 27 publications
23
174
4
10
Order By: Relevance
“…HbA1c level increased with BMI in our study but it was poorly correlated with BMI in the JDCS. Other studies have reported that diabetic patients with obesity had poor control of blood glucose, blood pressure and serum lipids, although they were more likely to be receiving antihypertensive drugs and lipidlowering drugs compared with non-obese patients [4,5]. In our study, patients in the older age group had glycemic, blood pressure and serum lipid control that was almost acceptable, even in those with BMI ≥30.…”
Section: Discussionsupporting
confidence: 52%
“…HbA1c level increased with BMI in our study but it was poorly correlated with BMI in the JDCS. Other studies have reported that diabetic patients with obesity had poor control of blood glucose, blood pressure and serum lipids, although they were more likely to be receiving antihypertensive drugs and lipidlowering drugs compared with non-obese patients [4,5]. In our study, patients in the older age group had glycemic, blood pressure and serum lipid control that was almost acceptable, even in those with BMI ≥30.…”
Section: Discussionsupporting
confidence: 52%
“…This is lower than the findings of Daousi et al (2006) which showed that 86% of the studied subjects were obese. It is also lower than the findings of the study done in Oyo State, Nigeria by Fadupin et al (2004) where it was found that 83.0% of the out-patients were either overweight or obese.…”
Section: Discussioncontrasting
confidence: 54%
“…Recent cross-sectional data revealed that 37% of 44 042 Swedish patients with type 2 diabetes had BMI X30 kg/m 2 ). 10 Other recent analyses have identified 75% of Brazilian type 2 diabetes patients as overweight (BMI425 kg/m 2 ) and 30% as obese, 11 while in the United Kingdom 12 and United States, 13 85 and 86%, respectively, were overweight and 52 and 55%, respectively, were obese. The prevalence of both obesity and diabetes is increasing rapidly.…”
Section: Role Of Obesity In the Pathogenesis And Management Of Typementioning
confidence: 99%